2017
DOI: 10.1186/s40814-017-0181-4
|View full text |Cite
|
Sign up to set email alerts
|

Optimising the acceptability and feasibility of novel complex interventions: an iterative, person-based approach to developing the UK Morita therapy outpatient protocol

Abstract: BackgroundThe aim of this paper is to showcase best practice in intervention development by illustrating a systematic, iterative, person-based approach to optimising intervention acceptability and feasibility, as applied to the cross-cultural adaptation of Morita therapy for depression and anxiety.MethodsWe developed the UK Morita therapy outpatient protocol over four stages integrating literature synthesis and qualitative research. Firstly, we conducted in-depth interviews combining qualitative and cognitive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 16 publications
0
28
0
Order By: Relevance
“…Other development teams using intervention mapping guidance have carried out extensive data gathering to elicit the views of patients, carers and different groups of health professionals but reported that the overall process was time-consuming and resource-intensive [66,67]. One development team carried out in-depth interviews and qualitative thematic analysis to influence intervention development [68]. It is unclear how much data might be considered sufficient and whether more data and extensive input from multiple stakeholders, as undertaken by such teams, ultimately equates to more effective interventions.…”
Section: Contact Voluntary Transport Servicesmentioning
confidence: 99%
“…Other development teams using intervention mapping guidance have carried out extensive data gathering to elicit the views of patients, carers and different groups of health professionals but reported that the overall process was time-consuming and resource-intensive [66,67]. One development team carried out in-depth interviews and qualitative thematic analysis to influence intervention development [68]. It is unclear how much data might be considered sufficient and whether more data and extensive input from multiple stakeholders, as undertaken by such teams, ultimately equates to more effective interventions.…”
Section: Contact Voluntary Transport Servicesmentioning
confidence: 99%
“…Therapists, in an effort to shift patients' attention away from symptom preoccupation and combat, will not focus on discussion or analysis of patients' symptoms or their causes, but will "steer" the conversation towards action-taking and the external environment Action-taking with symptoms Patients learn to undertake purposeful and necessary action, with or without their symptoms; action which is driven by "desire for life" rather than a desire to change internal states. MT thus aims to improve everyday functioning in spite of symptoms, with symptoms reducing as a by-product of moving from a mood-oriented to purpose-oriented and action-based lifestyle and randomised them to receive TAU or TAU plus 8-12 sessions of MT delivered by trained therapists at the University of Exeter's AccEPT clinic following our MT clinical protocol [38]. With the participant's consent, we audio-recorded all therapy sessions.…”
Section: Setting Recruitment and Data Collectionmentioning
confidence: 99%
“…For MT participants, we recorded the number of therapy sessions attended and reason for ending treatment. We completed post-treatment semi-structured interviews with consenting MT participants (n = 28) to explore their views of MT using a topic guide based on recent mental health trials addressing similar questions [13,52,53], MT literature and our MT optimisation study findings [38]. With participants' permission, interviews were audio-recorded and transcribed verbatim.…”
Section: Setting Recruitment and Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…It follows on from a programme of work conducted with patients and therapists to develop our Morita Therapy clinical protocol. 40 Findings from qualitative and mixed-methods work undertaken alongside the trial, to explore the acceptability of Morita Therapy and how this relates to treatment adherence, are reported elsewhere.…”
Section: Introduction and Objectivesmentioning
confidence: 99%